CHALLENGES OF AL ISLAM AND KEMUHAMMADIYAHAN (AIK) LEARNING WITH BAITUL ARQAM MODEL - Tri Santoso; Giyoto Giyoto; Baidi Baidi; Hari Kusmanto (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aimed to describe the implementation of AIK learning program with the Baitul Arqam model at the Muhammadiyah University of Surakarta in the 2019/2020 year. This study employed a qualitative approach to research. In collecting data, this study used observation, in-depth interviews, and documentation techniques, while the data validation was a triangulation of data sources and theories. This study's data analysis applied a CIPP Stufflebeam analysis. The results showed that (1) evaluating the AIK learning program with the Baitul Arqam model can be stated quite well in planning, organization, and implementation. The evaluation results on the supervision aspect of AIK learning program within the Baitul Arqam model can be unfavorable. Supervision was carried out only when students follow Baitul Arqam. Maintenance carried out after following the AIK learning with the Baitul Arqam model was not held. (2) The challenges faced by the AIK learning program with the Baitul Arqam model included: (a) the need for strategic planning, (b) qualified educators based on the standards, (c) a campus environment, and (d) an integrated supervision model.